Challenges in the management of patients with systemic light chain (AL) amyloidosis during the COVID‐19 pandemic. (4th July 2020) - Kastritis, Efstathios; Wechalekar, Ashutosh; Schönland, Stefan; Sanchorawala, Vaishali; Merlini, Giampaolo; Palladini, Giovanni; Minnema, Monique; Roussel, Murielle; Jaccard, Arnaud; Hegenbart, Ute; Kumar, Shaji; Cibeira, Maria T.; et al.
Summary: The severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2)‐associated coronavirus disease 2019 (COVID‐19) is primarily manifested as a respiratory tract infection, but may affect and cause complications in multiple organ systems (cardiovascular, gastrointestinal, kidneys, haematopoietic and immune systems), while no proven specific therapy exists. The challenges associated with COVID‐19 are even greater for patients with light chain (AL) amyloidosis, a rare multisystemic disease affecting the heart, kidneys, liver, gastrointestinal and nervous system. Patients with AL amyloidosis may need to receive chemotherapy, which probably increases infection risk. Management of COVID‐19 may be particularly challenging in patients with AL amyloidosis, who often present with cardiac dysfunction, nephrotic syndrome, neuropathy, low blood pressure and gastrointestinal symptoms. In addition, patients with AL amyloidosis may be more susceptible to toxicities of drugs used to manage COVID‐19. Access to health care may be difficult or limited, diagnosis of AL amyloidosis may be delayed with detrimental consequences and treatment administration may need modification. Both patients and treating physicians need to adapt in a new reality.